Penggunaan Fantasy Themes Tentang Pemberdayaan Perempuan Generasi Muda Melalui Media Digital di Komunitas ‘Puan Bisa’ - Alya Bunga Saharani; Fachrisa Alma Tiara Putri; Aditya Eka Putra (Jurnal Komunikasi Nusantara, 2023)
The online community 'Puan Bisa' is a women-specific community that has the goal of empowering women, especially young women by utilizing symbolic fantasy in digital communication. The fantasy theme is the contents of messages in communication that have been dramatized, either through the choice of words, phrases, slogans and so on. The purpose of this research is to find out what kind of fantasy themes and messages the founder of the 'Puan Bisa' community uses to members of the 'Puan Bisa' online community board in building group awareness. The goal of this research is to find out what kind of message is used by founder of the 'Puan Bisa' community. The method used in this research is descriptive qualitative with data collection in the form of interviews with informants, pattern matching, literature studies, and internet research. The results of this study show that the fantasy created by the Founder of the 'Puan Bisa' community for members of the online community 'Puan Bisa' has built a group awareness in carrying out and describing women's empowerment. This causes a fantasy chain to occur which gives rise to certain types of fantasy that have specific meanings when used within the women's empowerment community. Abstrak Komunitas online ‘Puan Bisa’ merupakan komunitas khusus perempuan yang mempunyai tujuan untuk memberdayakan perempuan khususnya perempuan muda dengan memanfaatkan fantasi simbolik dalam komunikasi digital. Tema fantasi merupakan isi pesan dalam komunikasi yang sudah didramatisasi, baik melalui pemilihan kata, frasa, slogan dan lain sebagainya. Tujuan dari penelitian ini untuk mengetahui tema fantasi dan pesan seperti apa yang digunakan pendiri komunitas ‘Puan Bisa’ kepada anggota pengurus komunitas online ‘Puan Bisa’ dalam membangun kesadaran kelompok. Metode yang digunakan pada penelitian ini adalah kualitatif deskriptif dengan pengumpulan data berupa wawancara terhadap informan, pola pencocokan, studi pustaka, dan riset internet. Hasil dari penelitian ini fantasi yang diciptakan oleh Pendiri dari komunitas ‘Puan Bisa’ kepada anggota pengurus komunitas online ‘Puan Bisa’ telah membangun sebuah kesadaran kelompok dalam melakukan dan menggambarkan pemberdayaan perempuan. Hal ini menyebabkan terjadinya rantai fantasi yang memunculkan tipe fantasi tertentu yang bermakna spesifik ketika digunakan di dalam komunitas pemberdayaan perempuan.